Investigating the Effectiveness of Podcasts as a Knowledge Sharing Tool for Poultry Farmers in Accra - Edwards, Philemon Kwasi (UniMAC, 2024)
This research study explores the effectiveness of podcasts as knowledge-sharing tool for poultry farmers in Accra. With the rapid growth of digital media, podcasts have emerged as a convenient alternative medium for disseminating information across various sectors, including agriculture. Using a qualitative research approach, the study explored how poultry farmers interact and patronize podcast technology for acquiring and sharing knowledge and best practices. Through the use of in-depth interviews with poultry farmers in Accra, the research investigated farmers experiences, challenges and perceptions regarding podcast usage in their agricultural practices. The study also assessed factors influencing podcast adoption, preferred content formats, and the impact of podcast-based learning on farming operations. Findings revealed key insights about the accessibility, usability and practical value of podcasts in the context of poultry farming knowledge dissemination. The research contributes to understanding how digital audio content can support agricultural education and information sharing in urban farming communities. Recommendations are provided for optimizing podcast content and delivery to better serve the knowledge needs of poultry farmers in Accra and similar urban agricultural settings.
MA Thesis
Keywords: Podcasts; Knowledge-sharing; Poultry Farming; Agricultural Education; Qualitative Research; Ghana